CHEMICAL HEALTH RISK ASSESSMENT IN THE METALLURGY DEPARTMENT OF A MINING COMPANY, INDONESIA : A CASE STUDY - Savira, Yenni Miranda; Susanto, Arif; Listiarini, Aprilia; Yochu, Wiliam Engelbert; Putro, Edi Karyono; Santoso, Danny Rosalinawati; Willmot, John Charles; Johan, Anita (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2023)
ABSTRACT Background: Miners are routinely exposed to various hazardous chemicals entering the body through inhalation, dermal, and ingestion. Although, likely, the long-term health impacts of certain chemicals will only become evident in years to come, the utilization of hazardous chemicals will continue to increase in the coming years, leading to a higher disease burden. Therefore, effective controls for the sound management of chemicals at the workplace shall be implemented. Purpose: This study aimed to assess the chemicals used and analyze the health risks related to the use of the chemicals in the flotation process. Methods: This study was a descriptive case study conducted in Indonesia's gold and copper mining company. We ran the assessment using the Chemical Health Risk Assessment method published by the Department of Safety and Health, Malaysia, Year 2018. The chemicals analyzed were limited to the reagents used in the flotation process in the metallurgy department, which have two possible exposure, inhalation, and dermal routes. Results: The results show three out of seven chemicals have the potential to expose workers through inhalation, which is categorized under medium risk, where xanthate has the highest risk rating (RR=12), which potentially causes health effects related to acute toxicity, specific target organs, and reproductive toxicity. Meanwhile, five out of seven chemicals have the potential to expose workers through dermal, where three chemicals fell into the high-risk category: promoter, frother, and lime (H2), and two chemicals fell into the moderate-risk category: xanthate and solutrix (M2). Adverse health effects from chemical exposures to dermal include irritation, corrosion, and sensitization. Conclusion: The reagents used in the flotation plant exhibited a significant health risk of inhalation and dermal contact with hazardous chemical exposure. The company shall evaluate the hazard and risk from the hazardous chemicals used in the flotation plant and implement adequate controls, considering elimination, substitution, engineering, administrative, and personal protective equipment (PPE) controls to minimize the workers' inhalation and dermal exposure.